JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Objective This study aimed to describe clinical characteristics, prognosis, and therapeutic approaches for central corneal degeneration syndrome (CCDS) in dogs. Animals 11 eyes from 9 client-owned dogs diagnosed with CCDS between 2015 and 2024. Clinical presentation CCDS was diagnosed on the basis of the presence of central corneal facets that progressively deepened and widened in the absence of corneal ulceration. Results The mean age at diagnosis was 14.2 years (range, 10 to 17 years). At the time of diagnosis, the facet depth was < 50% in 5 eyes, between 50% and 90% in 4 eyes, and > 90% in 2 eyes. The lesions were located in the axial cornea in 5 eyes and in the paraxial cornea in 6 eyes. At the final follow-up (mean follow-up period, 500.2 days; range, 87 to 1,195 days), progression of the facet depth to > 90% was observed in 10 of 11 eyes. Corneal perforation occurred in 3 eyes, and 2 unperforated eyes underwent corneoconjunctival transposition, resulting in restoration of normal corneal thickness. Clinical relevance CCDS is a rare condition in dogs, characterized by progressive thinning of the axial or paraxial corneal stroma without evidence of corneal ulceration, leading to the formation of corneal facets, potentially resulting in corneal perforation. Our findings suggested that CCDS occurs exclusively in older dogs and may be bilateral in some cases. When there is a risk of corneal perforation, surgical intervention, such as corneoconjunctival transposition, is recommended.